2012
DOI: 10.1155/2012/156975
|View full text |Cite
|
Sign up to set email alerts
|

Is Near-Infrared Spectroscopy a Reliable Method to Evaluate Clamping Ischemia during Carotid Surgery?

Abstract: Guidelines do not include cerebral oximetry among monitoring for carotid endarterectomy (CEA). The purpose of this study was to evaluate the reliability of near-infrared spectroscopy (NIRS) in the detection of clamping ischemia and in the prevention of clamping-related neurologic deficits using, as a cutoff for shunting, a 20% regional cerebral oxygen saturation (rSO2) decrease if persistent more than 4 minutes, otherwise a 25% rSO2 decrease. Bilateral rSO2 was monitored continuously in patients undergoing CEA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 22 publications
1
50
0
Order By: Relevance
“…Use of intraluminal shunt and general anesthesia are routinely recommended in most studies, but unpleasant complications during placement of shunt into the internal carotid artery are well known. [20][21][22][23][24] Anesthesia is the one of the most controversial issues of carotid endarterectomy. Detailed studies have reported cervical blockage has better results concerning perioperative stroke and cardiac events, such as arrhythmia and infarction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Use of intraluminal shunt and general anesthesia are routinely recommended in most studies, but unpleasant complications during placement of shunt into the internal carotid artery are well known. [20][21][22][23][24] Anesthesia is the one of the most controversial issues of carotid endarterectomy. Detailed studies have reported cervical blockage has better results concerning perioperative stroke and cardiac events, such as arrhythmia and infarction.…”
Section: Resultsmentioning
confidence: 99%
“…Intraluminal shunt use increased 20% to 25% in studies using EEG for cerebral monitoring, while 7% decrease was observed in patients who underwent carotid endarterectomy under regional anesthesia, which allows evaluation of consciousness and responses. [22,23] Furthermore, EEG cannot always detect perioperative cerebrovascular events. Regional anesthesia and awake patient provide precise information and evaluation, facilitating decision about shunt according to the case.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet it has been criticized for the wide range of values in normal conditions and for the lack of a clear cut-off value. Furthermore, many confounding factors may influence regional brain saturation, such as modification of systemic oxygen saturation and blood pressure or bronchodilation (16).…”
Section: Discussionmentioning
confidence: 99%
“…It has also shown its correlation with EEG changes, transcranial Doppler, carotid stump pressure and postoperative neurological deficits [29,[30][31][32][33]. The sensitivity of this test ranges from 30 to 100% according to various studies and its specificity between 77 and 98% [29,[30][31][32][33][34][35][36].…”
Section: Near Infrared Spectroscopy (Nirs)mentioning
confidence: 94%